LITERATURE REVIEW OF THE COUNSELOR’S ROLE IN DEALING WITH BULLYING IN SCHOOLS - A Malek, Mohd Ahsani bin (Universitas Muria Kudus, 2024)
Bullying at school is a serious problem that can negatively impact student’s social, emotional and academic development. School counselors have an important role in preventing and handling bullying. This research aims to examine literature review method by examining scientific articles, journals, books and other relevant sources published in the last 10 years. Keywords used in the literature search included “bullying”, “school counselor”, “intervention”, “prevention”, and “counseling”. Data analysis was carried out qualitatively by identifying main themes related to the role of counselors in dealing with bullying. The literature shows that school counselors play a role ini: (1) designing and implementing bullying prevention programs, such as life skills training and character education; (2) providing crisis intervention for victims of bullying including individual and group counseling; (3) providing counseling for bullies to change aggressive behavior; and (4) collaborating with teachers, parents and other parties in creating a save and inclusive school environment. Studies show the effectiveness of counselor interventions in reducing bullying and improving student well-being. However, further research is needed regarding intervention models that are appropriate to the Indonesian context. School counselor have a crucial role in dealing with bullying. Capacity building and support is needed for counselors to be able to carry out their role optimally.